Regional Cabdin Policy Contributions III and Evaluation of Work Discipline Performance of Honorary Teachers in State High Schools in Solok City - Nofianti . R; Asmendri Asmendri; M Haviz (Edumaspul: Jurnal Pendidikan, 2023)
This research is motivated by the results of the author's observations in public high schools in Solok City regarding the performance of honorary teachers, where it is seen that the performance level of honorary teachers is still very low. In this case, of the many factors that influence the performance of honorary teachers, the policies of the superiors, in this case the Head of Region III Regional Office and evaluation of work discipline, are factors that have a major influence on the performance of honorary teachers. The purpose of the study was to determine (1) the contribution of Regional III (X1) Regional Headquarters policy to the performance of honorary teachers (Y) in SMA Negeri Kota Solok, (2) the contribution of work discipline evaluation (X2) to the performance of honorary teachers (Y) in SMA Negeri Kota Solok, and (3) the contribution of regional III (X1) Head of Civil Engineering Policy and evaluation of work discipline (X2) on the performance of honorary teachers (Y) in SMA Negeri Kota Solok. This type of research is field research with a quantitative approach to the correlational method. The data analysis technique uses multiple linear regression analysis techniques. The population of the study was 53 honorary teachers at Solok State Senior High School. The research sample was selected by total sampling technique, because the total population is less than 100 people. The research instrument was a questionnaire about Region III Head of Regional Office Policy, evaluation of work discipline and honorary teacher performance, by using a Likert scale. Data were analyzed using multiple regression analysis techniques with the help of SPSS version 20.0. Based on data processing, the results are (1) there is a significant and positive contribution of X1 to Y with a strong category indicated by a significant value of 0.000 <0.05, so that H0 is rejected and Ha is accepted, (2) there is a contribution of X2 to Y indicated by a significant value 0.000 <0.05 so that H0 is rejected and Ha is accepted, (3) there is a significant and positive contribution of X1 and X2 to Y with a strong category indicated by a significant 0.000 <0.05, so H0 is rejected and Ha is accepted. The results of these findings can be concluded that the policies of Regional III Regional Office and Evaluation of work discipline are two factors that have contributed to the performance of honorary teachers in SMA Negeri Kota Solok.